Association between gene polymorphism of folate metabolism and recurrent spontaneous abortion in Asia: A Meta-analysis. Issue 40 (2nd October 2020) - Zhao, Xiaoxuan; Zhao, Yang; Ping, Yunlu; Chen, Lu; Feng, Xiaoling
Abstract : Abstract: To evaluate the association between gene polymorphisms of MTHFR (C677T, A1298C) and MTRR (A66G), and the recurrent spontaneous abortion (RSA) risk in Asia. Related case-control studies were collected, selected, and screened. A meta-analysis was conducted by Stata 12.0 software to assess the association between polymorphisms of target genes and RSA. Altogether 30 studies examining the relationship between genetic polymorphism of folate metabolism and RSA risk were included, among which 20 studies were related to MTHFR C677T, 11 to MTHFR A1298C and 6 to MTRR A66G. The studies suggested that MTHFR C677T polymorphism was closely connected with RSA risk under all models ( P < .05). Furthermore according to the subgroup analysis of ethnicity, the correlation between C677T polymorphism and RSA was stronger in north of China when compared with south of China and other Asian countries ( P > . 05). For MTHFR A1298C, it was closely related to RSA risk in all gene models except for (AC vs AA) ( P < .05). However, when it comes to MTRR A66G, there was no significant correlation between gene A66G polymorphism and RSA risk except for the additive gene model (G vs A) ( P < .05). The present evidence shows that the correlation between gene polymorphisms and RSA risk can be found in MTHFR C677T, A1298C (except for heterozygote model) and MTRR A66G (only in additive genotypes), and the detection of the correlated gene polymorphisms mentioned above is of certain guiding significance for preventing RSA and screening high-risk groups.